2013
DOI: 10.2174/1566524011313040006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Targeting as a Therapeutic Strategy Against Glioma

Abstract: Glioblastoma multiforme (GBM), the most common and aggressive form of primary brain tumor, presents a dismal prognosis. Current standard therapies are only able to improve patient survival by a few months. The search for alternative approaches in glioblastoma treatment, together with the recent discovery of a new class of small RNA molecules that are capable of regulating gene expression, prompted a race for a deeper and thorough understanding of how these molecules work. Today, it is known that microRNAs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Studies have demonstrated that miRNAs influence the response to chemotherapies for ovarian cancer, pancreatic cancer, bladder cancer and glioblastoma [37-40]. In a study conducted by Liana Adam, miR-200 expression regulated the epithelial-to-mesenchymal transition in bladder cancer cells and reversed EGFR therapy resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that miRNAs influence the response to chemotherapies for ovarian cancer, pancreatic cancer, bladder cancer and glioblastoma [37-40]. In a study conducted by Liana Adam, miR-200 expression regulated the epithelial-to-mesenchymal transition in bladder cancer cells and reversed EGFR therapy resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…9 Yet, functional delivery of these targeted treatments without the use of viral vectors is yet to be successful. Cell-based delivery mechanisms have become an attractive method for delivering miR and anti-miR for therapies, particularly through stem cells, due to their tropism to the region of GBM cells.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, a growing body of evidence indicates that miRNAs play fundamental roles in the tumorigenesis of human cancer including glioma, affecting cell survival, proliferation, differentiation, metabolism, angiogenesis, and stem cell generation [3, 4]. More and more numbers of miRNAs including miR-21, miR-125b, let-7, miR-9, and miR-137, as tumor suppressors or oncogenes by negatively regulating oncogenes or tumor-suppressor genes, have been verified to expose aberrant expression in glioma [59].…”
Section: Introductionmentioning
confidence: 99%